A novel examination of limonene detection using plastic fiber optic sensors and the tapered approach - Thanigai Anbalagan; Hazura Haroon; Hazli Rafis Abdul Rahim; Siti Halma Johari; Siti Khadijah Idris@ Othman; Hanim Abdul Razak; Maisara Othman (Institute of Advanced Engineering and Science, 2023)
A novel tapered plastic optic fiber (POF) biosensor is proposed and demonstrated for monitoring limonene in different concentrations. The mechanism of this device is based on an increase in the light transmission of a sensor submerged in a higher-concentration limonene solution, which also reflects an increase in the refractive index of the sensor. The tapered POF was fabricated using the chemical etching method to accomplish different waist diameters of 0.6 mm, 0.55 mm, and 0.5 mm, with a fiber length of 10 cm and a 2 cm sensing region. An Arduino integrated development environment (IDE) program was used to drive the voltage values from the photodetectors to obtain the measurements. As the limonene concentration solution varied from 20% to 100%, the output voltage of the sensor increased linearly, showing a sensitivity of 0.295 V/%, 0.33 V/%, and 0.46 V/% for tapered waist diameters of 0.6 mm, 0.55 mm, and 0.5 mm, respectively. The proposed sensor is a low-cost solution measurement option with high sensitivity, while it also involves a simple and easy fabrication technique.